2015
DOI: 10.1515/ijdhd-2015-0405
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and realms of service leadership and leadership models

Abstract: This paper presents a lesson plan in a course entitled "Service Leadership" at The Hong Kong Polytechnic University. In that lecture, three basic aspects of the service leadership model are presented. First, the origin of service leadership from an evolutionary anthropology perspective is outlined. Second, three realms of service leadership with reference to self, others and systems are presented. Third, two leadership models (i.e. topdown and bottom-up models) are introduced, and their strengths and weaknesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Patterson (2003) identified Servant-Leadership as giving of oneself, requiring the leader to be generous in aspects such as time, energy, care, compassion, and maybe even personal belongings. Shek et al (2015) presented Service Leadership as satisfying needs for self, others, communities, systems, and environments by providing quality personal service. The service leader is considered an on-the-spot entrepreneur with moral character and a caring disposition (Shek et al, 2015).…”
Section: Service-before-self and Servant-leader Attributes Of Service...mentioning
confidence: 99%
See 4 more Smart Citations
“…Patterson (2003) identified Servant-Leadership as giving of oneself, requiring the leader to be generous in aspects such as time, energy, care, compassion, and maybe even personal belongings. Shek et al (2015) presented Service Leadership as satisfying needs for self, others, communities, systems, and environments by providing quality personal service. The service leader is considered an on-the-spot entrepreneur with moral character and a caring disposition (Shek et al, 2015).…”
Section: Service-before-self and Servant-leader Attributes Of Service...mentioning
confidence: 99%
“…Shek et al (2015) presented Service Leadership as satisfying needs for self, others, communities, systems, and environments by providing quality personal service. The service leader is considered an on-the-spot entrepreneur with moral character and a caring disposition (Shek et al, 2015). Shek et al suggested that Service Leadership goes beyond existing concepts of leadership because the emphasis is on leading self and others.…”
Section: Service-before-self and Servant-leader Attributes Of Service...mentioning
confidence: 99%
See 3 more Smart Citations